Topographical art and historical geography: amateur English representations of Ligurian landscape in the early nineteenth century - Piana, Pietro; Watkins, Charles; Balzaretti, Ross (Centro Italiano per gli Studi Storico-Geografici, 2018)
This paper assesses the value of amateur topographical art for historical geographers and landscape historians. It examines the work of two amateur artists, Elizabeth Fanshawe and William Strangways, made in Liguria, northwest Italy, to assess the value of topographical art for understanding past landscapes. The identification and examination of the views takes advantage of a multidisciplinary approach which involves the use of historical cartography, oral history, written documents and field surveys. Three detailed case studies are used which provide insights into the landscape perception of early nineteenth-century foreign tourists and the cultural context in which they were produced. The determination of precise location allows rapidly sketched drawings to be understood and interrogated at the places they depicted. We argue that by grounding the drawings in this way we can add value both to the interpretation of the drawing itself and our understanding of the place it represents.